A multilevel investigation of predictors and outcomes of shared leadership - Kai N. Klasmeier; Jens Rowold (Journal of Organizational Behavior, 2020)
For modern organizations, shared leadership becomes increasingly important. Knowledge on shared leadership may be limited, as past research often relies on cross-sectional data or student samples, and most studies neglect the multilevel nature of shared leadership. Our research model includes transformational leadership, trust, and organizational support as predictors of shared leadership. Furthermore, we analyze the influence of shared leadership on team performance and team creativity. In total, 160 teams with 697 employees participated in our field study. Data collection took place at three time points. To test our hypotheses, we used multilevel modeling with a Bayesian estimator. We found relationships of transformational leadership and trust with shared leadership at the team level and of transformational leadership, trust, and organizational support with shared leadership at the individual level. Furthermore, shared leadership fully mediated the effect of the three input factors on team performance and team creativity. This study contributes to the understanding of the antecedents and outcomes of shared leadership. Furthermore, the dynamic development of team processes based on an input–mediator–output model is explored. On the basis of the results, organizations can increase shared leadership behavior by focusing on transformational leadership and trust building.
Keywords: 650; Bayes; multilevel; shared leadership; team creativity; team performance